Does access to health insurance reduce the risk of miscarriages? Evidence from Mexico's Seguro popular - Tobias Pfutze (Latin American Economic Review, 2015)
This paper analyzes whether Mexico's de-facto non-contributory health insurance program Seguro Popular had an effect on the risk of miscarriage during pregnancy. Using data on pregnancies over the 2004-08 period from the 2009 round of the National Survey on Demographic Dynamics (ENADID), and employing the staggered roll-out of the program as an identification strategy, it is found that it resulted in a significant reduction in the risk of a miscarriage. For the target population, a one percentage point increase in eligibility is found to decrease miscarriages by .04 percentage point at the average.
Keywords: I13; I15; I18; O12; 330; Miscarriages; Health insurance; Mexico